PENGARUH KOMITE AUDIT, UKURAN PERUSAHAAN, TINGKAT HUTANG PERUSAHAAN, PROFITABILITAS, INTENSITAS KEPEMILIKAN ASET TETAP DAN INTENSITAS PERSEDIAAN TERHADAP MANAJEMEN PAJAK DENGAN INDIKATOR TARIF PAJAK EFEKTIF (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di BEI Tahun 2015-2017) - Yena Repwita, Yena Repwita; Zirman, Zirman; Rusli, Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This research to analyze the effect of Audit Committee, Size, Leverage,Profitability, Capital Intensity Ratio and Inventory Intensity Ratio to taxmanagement using effective tax rates as a indicator On ManufacturingCompanies.This research uses Purposive Sampling Technique in which this studytakes data from manufacturing companies listed In Indonesia Stock Exchange2015-2017. The population in this study were 154 manufacturing companies,samples were selected from the population based on the research criteria whichwere as many as 59 companies with a period of 3 years so that the total samplewas 177 samples. Hypothesis testing is done by using multiple linear regressiontests. Data analysis conducted with multiple regression model with help ofsoftware SPSS version 23. The results of the research indicate that the AuditCommittee and size have no effect on the effective tax rate. While the Leverage,Profitability, Capital Intensity Ratio and Inventory Intensity Ratio have an effecton the effective tax rate (t Test). The results of the f test show that the AuditCommittee, Size, Leverage, Profitability, Capital Intensity Ratio and InventoryIntensity Ratio simultaneously have a significant effect on the effective tax rate.The results of the coefficient of determination show that 13.3% of the independentvariables influence the dependent variable and the remaining 86.7% is influencedby other variables not included in this study.Keywords : Audit Committee, Size, Leverage, Profitability, Capital Intensity Ratio,Inventory Intensity Ratio, Effective Tax Rates